Synthesis and characterization of capsule shells non gelatin grass jelly leaves-seaweed as drug delivery system material - Micha Mahardika; Fauzan Amin; Ika Agustia Umami; Boima Situmeang; Agus Malik Ibrahim (Jurnal Pendidikan Kimia (JPKim), 2021)
Drug delivery system is a system that describes the journey of a drug to its target location.  The main component of the drug delivery system is gelatin. The leaves of grass jelly-seaweed are needed as a raw material for gelatin. The main component of gelling agents in grass jelly leaves and seaweed is a low-methoxy pectin polysaccharide. Pectin from previous study is used as a synthesis material for hard capsule shells with the addition of other ingredients, which are Na-CMC, sorbitol, and water. The characterization results of capsule shells with variations in the composition of grass jelly-seaweed leaves 0: 4, 1: 3, 2: 2, 3: 1, and 4: 0 (A, B, C, D and E) have a disolving time of 12 minutes 45 seconds; 15 minutes 53 seconds; 23 minutes 10 seconds; 15 minutes 35 seconds and 18 minutes 12 seconds. The swelling degree test each of 200%;  266,7%;  303.3%;  586.7% and 643.3%. Furthermore, the shells of grass jelly-seaweed leaf capsules were tested for their material performance in the cefadroxyl disolving test with variations in sampling time of 10, 20, and 30 minutes.Keywords: Cefadroxyl, Drug delivery system, Green grass jelly leaves, Non-gelatin capsules, Seaweed